Turnout and closeness: Evidence from 60 years of Bavarian mayoral elections - Felix Arnold (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
One prediction of the calculus of voting is that electoral closeness positively affects turnout via a higher probability of one vote being decisive. I test this theory with data on all mayoral elections in the German state of Bavaria between 1946 and 2009. Importantly, I use constitutionally prescribed two-round elections to measure electoral closeness and thereby improve on existing work that mostly uses ex- post measures that are prone to endogeneity. The results suggest that electoral closeness matters: A one standard deviation increase in close- ness increases turnout by 1.68 percentage points, which corresponds to 1 6 of a standard deviation in this variable. I also evaluate how other factors like electorate size or rain on election day affect turnout differentially depending on the closeness of the race.
Keywords: D72; H70; 330; Turnout; Closeness; Mayoral Elections; Bavaria; Two-Round Ballot